An Evaluation of the Importance of Mysis relicta to the Lake Superior Fish Community - Isaac, Edmund Jacob (2010)
University of Minnesota M.S. thesis. May 2010. Major: WAter Resources Science. Advisor: Dr. Thomas R. Hrabik, Dr. Jason D. Stockwell. 1 computer file (PDF); vi, 85 pages. Mysis relicta is a major prey item for many fish species in Lake Superior, However, its importance to an entire fish community as a whole has not been quantified. We describe seasonal prey selection of the major fish species collected across 18 sites in Lake Superior, and again at five locations in western Lake Superior in 2006 using a selection index (Chesson's Alpha). We also used bioenergetics models to estimate the consumption of prey items by the fish community at the same locations. Additionally, we modeled the production of Mysis, to evaluate this prey resource in terms of demand and supply. We found that rainbow smelt, kiyi, and bloater selected for Mysis over other prey items during all seasons, while lake whitefish only selected for Mysis in the spring and summer. Cisco selected for large zooplankton, while all three sculpin species exhibited neutral selection of prey items. Burbot and siscowet selected for deepwater sculpin and Mysis during all seasons, with juveniles showing a stronger selection for Mysis than did adults. Mysis was the most consumed prey item lakewide, with higher annual consumption offshore than nearshore. Predation on Mysis was mainly from rainbow smelt, bloater, and lake whitefish nearshore, and deepwater sculpin and kiyi offshore. Our estimates of Mysis production (supply) were higher than the consumptive demand by the fish community at nearly all locations, with this balance indicating stability in the food web. Mysis relicta was found to be a sought after prey item by many fish species, and is directly responsible in supporting the fish communities both nearshore and offshore. Thus, Mysis plays a pivotal role in the structure and function of the Lake Superior fish community.